2019
DOI: 10.1016/j.ajhg.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

TRIDENT-2: National Implementation of Genome-wide Non-invasive Prenatal Testing as a First-Tier Screening Test in the Netherlands

Abstract: The Netherlands launched a nationwide implementation study on non-invasive prenatal testing (NIPT) as a first-tier test offered to all pregnant women. This started on April 1, 2017 as the TRIDENT-2 study, licensed by the Dutch Ministry of Health. In the first year, NIPT was performed in 73,239 pregnancies (42% of all pregnancies), 7,239 (4%) chose first-trimester combined testing, and 54% did not participate. The number of trisomies 21 (239, 0.33%), 18 (49, 0.07%), and 13 (55, 0.08%) found in this study is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
305
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(357 citation statements)
references
References 45 publications
28
305
2
3
Order By: Relevance
“…One of the main study limitations was that this was a selected set of pregnancy samples and thus may not be truly representative of a larger general pregnancy population. Other recent publications have looked at genome-wide NIPT in patient populations of at least 10,000 patients [5,6,34,43], with a few publications reporting results from populations of over 50,000 patients [28,44,45]. However, the observed assay failure rate and FF distribution in our study population were consistent with those observed in the referral population, suggesting the data is representative.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…One of the main study limitations was that this was a selected set of pregnancy samples and thus may not be truly representative of a larger general pregnancy population. Other recent publications have looked at genome-wide NIPT in patient populations of at least 10,000 patients [5,6,34,43], with a few publications reporting results from populations of over 50,000 patients [28,44,45]. However, the observed assay failure rate and FF distribution in our study population were consistent with those observed in the referral population, suggesting the data is representative.…”
Section: Discussionsupporting
confidence: 83%
“…In our cohort, even if the number is too small to draw definitive conclusions, this strategy is particularly interesting in the low-risk population (first-tier screening) because four of the five anomalies belonged to Groups 2 and 3. If we reanalyze the cohort presented in the recent study of the Dutch NIPT Consortium [28], only 47 women would have received a positive NIPT call for RAAs instead of 101, and all cases with fetal RAAs would have been diagnosed. In our study, targeting SUAs and trisomies 8, 9, 12, 14, 15, 16, and 22 only would generate a positive NIPT call rate of 0.57% (17/3007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the first year of GW-cfDNA testing in The Netherlands (TRIDENT-2 study) included 56 818 women who underwent GW-cfDNA testing, from an initial cohort of 73 239 women who had a cfDNA test; in 207 (0.4%) of these women, the test was positive for RATs (n = 101), SIs (n = 95) or complex abnormal profiles (n = 11) 3 . Among the 101 RATs, six were confirmed but only one of these was associated with an abnormal phenotype.…”
mentioning
confidence: 99%
“…Genome-wide NIPT was performed as part of the Dutch Trident 2 study (Trident = Trial by Dutch laboratories for Evaluation of NIPT), using shallow massively parallel sequencing and WISECONDOR for analysis. 5 The four cases presented here involved one case of trisomy 5 and trisomy 7 and three cases of trisomy 8. According to our local protocol, a CVS was recommended, which was performed transabdominally in all cases.…”
mentioning
confidence: 90%